2016
DOI: 10.18632/oncotarget.9693
|View full text |Cite
|
Sign up to set email alerts
|

Association between the APEX1 Asp148Glu polymorphism and prostate cancer, especially among Asians: a new evidence-based analysis

Abstract: BackgroundProstate cancer (Pca) is a serious disease associated with considerable morbidity and mortality. As a causative factor, the Asp148Glu polymorphism has been identified in the apurinic/apyrimidinic endonuclease (APEX1) gene. However, the association among Asians is considered controversial.MethodsEvidence for this association was obtained from the PubMed, Embase, HuGENet and Chinese National Knowledge Infrastructure (CNKI) databases. In the analysis, four models were applied. Associations between the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…Inclusion criteria: (1) the type of study was case-control; (2) cases were histologically diagnosed with PC patients, the pathological type was adenocarcinoma, control group was unrelated healthy people; (3) the distribution of genotypes was fully justified with Hardy-Weinberg genetic balance law; (4) the literature provided a complete genotype data. Exclusion criteria: (1) there was only case but without control group; (2) study which was repetitive publication; (3) incomplete data [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion criteria: (1) the type of study was case-control; (2) cases were histologically diagnosed with PC patients, the pathological type was adenocarcinoma, control group was unrelated healthy people; (3) the distribution of genotypes was fully justified with Hardy-Weinberg genetic balance law; (4) the literature provided a complete genotype data. Exclusion criteria: (1) there was only case but without control group; (2) study which was repetitive publication; (3) incomplete data [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…34,[42][43][44][45] A recent meta-analysis study revealed a statistically significant of the APEX1 (rs1130409*p.Asp148Glu) variant with the progression of prostate cancer under dominant (OR = 1.159, 95% CI = 1.000-1.159) model. 43 Another meta-analysis report indicated that the APEX1 (rs1130409*p.Asp148Glu) variant could represent an independent risk factor with different types of cancers under dominant (OR = 1.09, p = 0.028) model. Moreover, upon subgroup stratification, the authors reported a significant association with this missense variant among Caucasian subjects under the dominant (OR = 1.11, p = 0.049) model.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it has a crucial role in the incision mechanism of the AP sites and the regulation of multiple epigenetic processes such as DNA methylation 7,23 . Numerous meta‐analysis studies explored the association of the APEX1 (rs1130409*p.Asp148Glu) variant with the susceptibility of different cancerous diseases but with problematic conclusions 34,42–45 . A recent meta‐analysis study revealed a statistically significant of the APEX1 (rs1130409*p.Asp148Glu) variant with the progression of prostate cancer under dominant (OR = 1.159, 95% CI = 1.000–1.159) model 43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A missense G → T substitution SNP in the APEX1 gene in exon 5 (rs1130409) changes a critical Asp → Glu residue at codon 148. An up to date report connects this SNP to the development of PCa in Asian descendents ( Chen et al. , 2016 ).…”
Section: Introductionmentioning
confidence: 99%